The Oxford handbook of criminology - Liebling, Alison; Maruna, Shadd; McAra, Lesley (Oxford University Press, 2023)
"With contributions from over 85 leading experts in the field, The Oxford Handbook of Criminology is the definitive guide to the discipline, providing an authoritative and outstanding collection of chapters on the key topics studied in criminology courses. The Handbook has shaped the study of criminology for over two decades and, with this new edition, continues to be indispensable to students, academics, and professionals alike. Each chapter details relevant theory, recent research, policy developments, and current debates, whilst comprehensive referencing aids further research. Extensively revised, the seventh edition has been expanded to include important areas such as victimology, sex offending, hate crime, cybercrime, atrocity, convict criminology, prison abolitionism, and comparative criminology." --